2002
DOI: 10.1038/sj.npp.1300054
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-Related Gene Polymorphisms and Central Nervous System Serotonin Function

Abstract: Central nervous system (CNS) serotonergic function affects a wide range of biological and behavioral functions affecting health and disease. Our objective in this study was to determine whether functional polymorphisms of the genes that encode for the serotonin transporter promoter (5HTTLPR) and monoamine oxidase A (MAOA-uVNTR) are associated with CNS serotonin turnoverFindexed by cerebrospinal fluid levels of 5-hydroxyindoleacetic acid (5-HIAA)Fin a community sample of healthy adults. Subjects were 165 commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
181
4
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(200 citation statements)
references
References 46 publications
11
181
4
4
Order By: Relevance
“…No reliable association was found between 5-HTLPR and the level of serotonin metabolite in the cerebrospinal fluid. 83,84 Lower availability of the 5-HT1A receptor in 5-HTTLPR s allele carriers has been reported and awaits replication. 85 While single measurements of 5-HTT availability and serotonin turnover have not provided a consistent picture, specific challenge tests may be better suited to reveal differences in central nervous reactivity associated with 5-HTTLPR.…”
Section: The Functionality Of 5-httlprmentioning
confidence: 99%
“…No reliable association was found between 5-HTLPR and the level of serotonin metabolite in the cerebrospinal fluid. 83,84 Lower availability of the 5-HT1A receptor in 5-HTTLPR s allele carriers has been reported and awaits replication. 85 While single measurements of 5-HTT availability and serotonin turnover have not provided a consistent picture, specific challenge tests may be better suited to reveal differences in central nervous reactivity associated with 5-HTTLPR.…”
Section: The Functionality Of 5-httlprmentioning
confidence: 99%
“…In a sample of 165 healthy volunteers, males with high activity alleles displayed higher 5-HIAA than males with low activity alleles, whereas no differences were detected among women. 29 Zahlsman et al 31 in a clinical sample of 98 subjects found that high activity genotypes were associated with high HVA among males. Finally, in a study conducted on 88 healthy volunteers Jonsson et al 30 found that high activity genotypes were associated with higher HVA and 5-HIAA metabolite levels in women, but with lower CSF HVA levels in men.…”
Section: Introductionmentioning
confidence: 97%
“…28 Since MAOA is one of the major enzymes responsible for monoamine degradation within the CNS, it is plausible to assert that functional variants within the gene might contribute to interindividual differences in brain monoamine activity that, in turn, might alter the risk of developing antisocial-related disorders. To date, only a few studies [29][30][31] have evaluated the influence of MAOA-LPR on CSF monoamine metabolite levels in humans, with controversial results. In a sample of 165 healthy volunteers, males with high activity alleles displayed higher 5-HIAA than males with low activity alleles, whereas no differences were detected among women.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that 5-HTTLPR polymorphisms moderate other monoamine metabolites, such as MHPG and HVA. Jonsson et al (1998) reported the relationship between 5-HTT polymorphisms and MHPG, although their results were not replicated (Williams et al, 2003). Furthermore, Å gren et al (1986) observed positive correlations between 5-HIAA and HVA in CSF and suggested a unidirectional relationship between 5-HIAA and HVA, from the former to the latter.…”
Section: Introductionmentioning
confidence: 97%